GAMBARAN GEJALA HIPOKSIA DAN WAKTU SADAR EFEKTIF DALAM RUANG UDARA BERTEKANAN RENDAH DI KETINGGIAN SETARA 25.000 KAKI PADA AWAK PESAWAT AKTIF LAKESPRA DR. SARYANTO TAHUN 2021 - Nabilla Tita Azalia Putri, (2023)
Hypoxia is a state of reduced oxygen in organ tissues which causes body tissues to fail to get adequate oxygen supply. Hypoxia can occur due to decreased oxygen tension in arterial blood and capillary blood, which is referred to as hypobaric hypoxia. Hypobaric hypoxia is generally recognized as the most serious physiological hazard during high-altitude flight. This puts active crew members at risk for hypoxia and so they rely on effective performance time (EPT) or time useful consciousness (TUC) to take appropriate corrective and protective actions when hypoxia occurs. This requires the flight crew to meet good EPT/TUC requirements (<4 minutes) which can be assessed during Hypobaric Chamber training at 25,000 feet. The altitude of 25,000 feet was chosen to avoid decompression sickness and is the peak profile of the hypoxic exercise. This study was conducted to describe the symptoms of hypoxia and EPT/TUC on active flight crew at Lakespra dr. Saryanto in 2021. A descriptive research design using medical record data from 99 flight crew with simple random sampling. The results showed that 18 people (18.2%) experienced cognitive symptoms, 4 people (4%) experienced psychomotor symptoms, 16 people (16.2%) experienced visual symptoms, 3 people (3%) experienced psychological symptoms, 54 people (54.5%) experienced non-spesific symptoms, and 37 people (37.4%) did not feel any symptoms. Most of the flight crew had sufficient EPT/TUC scores (3-4 minutes), namely 68 people (68.7%).